Проблемы синергии художественного текста (на материале англоязычных текстов Дж. Джойса, О. Уайльда и Ж.-К. Гюисманса) - Фоменко, Е. Г.; Фоменко, Олена Геніївна; Fomenko, E. G. (My University, 2016)
Стаття досліджує ризики, пов’язані з предметом дослідження, термінологією та продуктивними методами синергії художнього тексту. Робиться висновок, що вивчення синергії письменника відкриває нові горизонти для розуміння світового художнього дискурсу, мовотворення якого вибудовує колективне фрактальне ціле. Розмежовуються художній текст і художній дискурс; з’ясовується роль індивідуально-авторської концепції у фазовому переході на матеріалі синергії {Дж. Джойс [О. Уайльд (Ж.-К. Гюісманс)]}.

The article studies the risks related to the subject of research, terminology and productive methods of fictional text synergy. The author arrives at the conclusion that the study of synergy of a writer opens up new horizons for comprehending world fictional discourse whose language creativity builds the collective fractal whole. This study distinguishes fictional text from fictional discourse, as well as identifies the role of individual-authorial conception in the phase shift based on the synergy {J. Joyce [O. Wilde (J.-K. Hyusmans)]}.
Фоменко Е. Г. Проблемы синергии художественного текста (на материале англоязычных текстов Дж. Джойса, О. Уайльда и Ж.-К. Гюисманса) / Е. Г. Фоменко // Одеський лінгвістичний вісник. - 2016. - Вип. 8. - С. 61-66.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; контекст-текст-підтекст; художній дискурс; синергія письменника; фазовий перехід; параметри порядку; турбулентність; індивідуально-авторська концепція; context-text-subtext; fictional discourse; synergy of writer; phase shift; parameters of order; turbulence; individualauthorial conception